Correction: Evaluating the competence of the primary vector, Culex tritaeniorhynchus, and the invasive mosquito species, Aedes japonicus japonicus, in transmitting three Japanese encephalitis virus genotypes. - Astri Nur Faizah; Daisuke Kobayashi; Michael Amoa-Bosompem; Yukiko Higa; Yoshio Tsuda; Kentaro Itokawa; Kozue Miura; Kazuhiro Hirayama; Kyoko Sawabe; Haruhiko Isawa (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0008986.].